ON THE FINITE GROUPS WITH AVERAGE LENGTH 3 OF CONJUGACY CLASSES - Du, Xianglin (Italian Journal of Pure and Applied Mathematics, 2013)
This article studies the problem of average length of conjugacy classes of finite groups, and classifies all finite groups with the average length 3 of conjugacy classes.